Green Synthesis, Characterization and Bioactivity of AuNPs from E. cardamomum: A Comparative Study - Sowmya, KM; Narendhirakannan, RT (International Journal of Pharmaceutical Investigation, 2025)
Background Nanoparticles, particularly those from natural sources like E. cardamomum, have garnered significant interest due to their unique physicochemical characteristics and potential applications in medicine. Materials and Methods This study explores the synthesis and characterization of Gold Nanoparticles (AuNPs) synthesized from E. cardamomum, focusing on their antibacterial, antioxidant and anti-inflammatory properties. Results and Discussion The green synthesis approach using extracts from cardamom seeds and pods facilitated the production of spherical AuNPs, confirmed by UV-vis spectroscopy, SEM, TEM, XRD, EDX and FTIR analysis. Comparative analysis revealed that AuNPs synthesized from cardamom pods exhibited superior antibacterial, antioxidant and anti-inflammatory activities compared to those from seeds. Antibacterial efficacy was evaluated through well-diffusion and MIC methods, highlighting concentration-dependent effects. Various antioxidant assays, including DPPH scavenging and FRAP, demonstrated potent radical scavenging capabilities. Additionally, assays for anti-inflammatory properties, such as albumin denaturation and hemolysis inhibition, underscored the nanoparticles' potential in mitigating inflammatory responses. Conclusion These findings underscore the therapeutic potential of AuNPs of E. cardamomum pods, suggesting their promise as lead candidates for developing novel treatments targeting microbial infections and oxidative stress-related conditions. This research contributes valuable insights into harnessing plant-mediated nanoparticles for medicinal applications, emphasizing their role in advancing pharmaceutical and biomedical sciences.
Keywords: Antioxidant, Anti-inflammatory; E. cardamomum; AuNPs, Nanoparticles